Curricular Approaches to Value Formation in Preschoolers from a Folkloric Perspective - Mihai, Cristina (Didactica Danubiensis, 2025)
Abstract Objectives: This paper examines the role of folklore as a foundational pedagogical resource for cultivating value orientations, cultural identity, and linguistic competence in preschoolers. It explores how the curricular integration of folkloric elements, a repository of traditions and values, can advance these formative aims and support holistic development in a globalized context. Prior Work: The study synthesizes established pedagogical theories, particularly systemic curriculum models emphasizing axiological dimensions. It also builds upon scholarship in folk pedagogy and ethnopedagogy, which recognize folklore as an essential medium for the intergenerational transmission of cultural heritage and identity formation. Approach: A qualitative, analytical methodology is applied, including a detailed content analysis of a national early childhood curriculum. Specific competencies, learning activities, and performance standards are mapped to folkloric categories such as literary, musical, choreographic, and ritualistic forms. A comparative review of international educational models provides additional context. Results: Findings from the content analysis indicate that a structured curriculum effectively integrates folklore across developmental domains. Activities like listening to carols, engaging in traditional dances, and crafting cultural artifacts promote personal and social development, language acquisition, and artistic expression. These activities also foster moral reasoning, cultural respect, and an appreciation for both national culture and diversity. Implications: For curriculum developers and teacher educators, these findings emphasize the necessity of integrating traditional pedagogical approaches into professional preparation. This equips future teachers to design culturally authentic, meaningful learning experiences that bridge heritage and contemporary practice. Value: This paper's primary contribution is the creation of a detailed theoretical framework and practical blueprint for systematically aligning folkloric content with standardized curricular objectives. It provides educators with a structured, non-anecdotal strategy for implementing value-laden education grounded in cultural heritage.